Use of the Social Vulnerability Index in Investigating Transit Deserts - Doustmohammadi, Mehrnaz (Advances in Social Sciences Research Journal, 2022)
Accurately predicting the true demand of transit is one of the most challenging and crucial matters that various departments of transportation are attempting to solve. One of the tools for predicting the demand and creating the proper infrastructures and facilities, is using a social vulnerability index (SVI). This index is developed using the vulnerability demographics of old age, poverty, vehicle ownership, crowded housing, and disability. The value of estimating demand using social vulnerability is to attempt to focus on individuals who are more likely to rely on transit for their means of transportation, as such, socially vulnerable demographics which limit an individual’s ability to traverse the network may be used by a decision-maker when attempting to allocate resources or investment towards underrepresented areas. The index is then used to identify potential transit deserts or areas in which demand exists but has no transit service. In this study, the index uses U.S. Census data to identify the most vulnerable counties for the state of Alabama. The areas designated as most vulnerable are areas with historic economic deficiency and tend to be more rural counties. Future research is required however to relate transit ridership to the vulnerability attributes selected. To this end, cooperation with state transit agencies is required to have a more in-depth understanding of the results.